Teologiczno-patriotyczny charakter jasnogórskich aktów zawierzenia św. Jana Pawła II - Józef Warzeszak (Studia Paradyskie, 2022)
In this article, the author discusses the acts of entrustment that John Paul II addressed to the Lady of Jasna Góra, Queen of Poland, “Mother of my nation” and “my homeland” during his pilgrimages to Poland. The Pope thanks in them for the blessed presence of Lady of Jasna Góra in Poland; expresses his closeness to suffering compatriots, especially those who suffered repressions by the communist regime. He commends to the caring hands of the Queen of Poland the future of children, youth, families, matters and social attitudes that has a key meaning for the future. In the content of the prayers, one can see the Pope’s great effort to build and strengthen Marian devotion and spirituality in the Polish nation as the foundations of its prosperous future. In a word, all these prayers and entrustments contain an enormous theological and patriotic treasury, so that it is worthwhile to conduct theological reflection on them.